Forming the Hematology-Oncology Collaborative Videoconferencing (CO-VID) Learning Initiative: Experiential Lessons Learned From a Novel Trainee-Led Multidisciplinary Virtual Learning Platform. Issue 1 (January 2022) - Martin, Richard L.; Grant, Michael J.; Kimani, Stephen; Midha, Shonali; May, Jori; Patell, Rushad; Collier, Emily; Furfaro, David; Bodine, Charles; Reap, Leo; Shah, Nikesh; DeLaune, Jess; et al.
Abstract : PURPOSE: COVID-19 challenged medical practice and graduate medical education. Building on previous initiatives, we describe and reflect on the formative process and goals of the Hematology-Oncology Collaborative Videoconferencing Learning Initiative, a trainee-led multi-institutional virtual COVID-19 learning model. METHODS: Clinical fellows and faculty from 13 US training institutions developed consensus needs, goals, and objectives, recruited presenters, and generated a multidisciplinary COVID-19 curriculum. Weekly Zoom conferences consisted of two trainee-led instructional segments and a trainee-moderated faculty Q&A panel. Hematology-oncology training program faculty and trainees were the targeted audience. Leadership evaluations consisted of anonymized baseline and concluding mixed methods surveys. Presenter evaluations consisted of session debriefs and two structured focus groups. Conference evaluations consisted of attendance, demographics, and pre- or postmultiple-choice questions on topic learning objectives. RESULTS: In 6 weeks, the initiative produced five conferences: antivirals, anticoagulation, pulmonology, provider resilience, and resource scarcity ethics. The average attendance was 100 (range 57-185). Among attendees providing both pre- and postconference data, group-level knowledge appeared to increase: antiviral (n = 46) pre-/postcorrect 82.6%/97.8% and incorrect 10.9%/2.2%, anticoagulation (n = 60) pre-/postcorrect 75%/93.3% and incorrect 15%/6.7%, and pulmonary (n = 21) pre-/postcorrect 66.7%/95.2% and incorrect 33.3%/4.8%. Although pulmonary management comfort appeared to increase, comfort managing of antivirals and anticoagulation was unchanged. At the conclusion of the pilot, leadership trainees reported improved self-confidence organizing multi-institutional collaborations, median (interquartile range) 58.5 (50-64) compared with baseline 34 (26-39), but did not report improved confidence in other educational or leadership skills. CONCLUSION: During crisis, trainees built a multi-institutional virtual education platform for the purposes of sharing pandemic experiences and knowledge. Accomplishment of initiative goals was mixed. Lessons learned from the process and goals may improve future disaster educational initiatives.